Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3390/su7066376
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Environmental Impacts of Peat Use for Electricity Generation in Ireland—A Life Cycle Assessment

Abstract: Abstract:The combustion of peat for energy generation accounts for approximately 4.1% of Ireland's overall greenhouse gas (GHG) emissions, with current levels of combustion resulting in the emission of 2.8 Mt of CO2 per annum. The aim of this research is to evaluate the life cycle environmental impacts of peat use for energy generation in Ireland, from peatland drainage and industrial extraction, to transportation, combustion, and subsequent after-use of the cutaway area, utilising Irish-specific emission fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Peat combustion is described in a previous study [104]. Data for fossil fuel combustion in the reference scenarios is from the econivent database [105,106].…”
Section: Life Cycle Assessment Datamentioning
confidence: 99%
“…Peat combustion is described in a previous study [104]. Data for fossil fuel combustion in the reference scenarios is from the econivent database [105,106].…”
Section: Life Cycle Assessment Datamentioning
confidence: 99%
“…The majority of the electricity from biomass is generated by co-firing with peat, to offset peat combustion. Peat combustion produces large volumes of CO 2 directly but also indirectly reduces the carbon budget of indigenous peatlands [5]. The uptake of solar power generation in the Irish renewable energy market to date has been low, accounting for less than 0.3% of total electricity generated in 2012 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 175,321 tonnes (1,349,969 GJ) of peat would need to be burnt to meet the energy input of the imported PKS and sunflower husk pellets. A previous study has shown that the harvesting and combustion of 1 GJ of peat results in the emission of 120 kg CO2-eq per GJ (Murphy et al, 2015a). Combustion of the same quantity of peat as the imported biomass co-fired would result in GHG emissions of 161,996 t CO2-eq, significantly lower than the emissions from imported biomass in the reference scenario (208,829 t CO2-eq) and the Post-COP21 scenario (155,.…”
Section: Comparison With Peat-only Combustionmentioning
confidence: 91%
“…Investigation of the potential impact of the Paris Agreement on national mitigation policies and the risk of carbon leakage; an analysis of the Irish bioenergy industry. Energy Policy,104,[80][81][82][83][84][85][86][87][88] of CO2 directly but also indirectly reduces the carbon budget of indigenous peatlands (Murphy et al, 2015a). Co-firing of biomass with peat is a key element of Ireland's renewable energy policy with the Government mandating each of the three peat-fired power plants to co-fire at a rate of 30% of the maximum rated capacity until 2017, 40% between 2017 and 2019, and 50% thereafter (Department of Communications Energy and Natural Resources, 2010).…”
Section: Irish Greenhouse Gas Emissions and Energy Policymentioning
confidence: 99%
See 1 more Smart Citation